The Language of Gángan, A Yorùbá Talking Drum - Akinbo, Samuel Kayode (Frontiers in Communication, 2021)
It is widely known that Yorùbá drummers communicate through their native drums. This paper investigates the grammar of gángan, which belongs to a family of Yoruba drums called dùndún. The results of this study show that Yorùbá drummers represent the phonetic realisation of lexical and grammatical tones of their language with the drum. Statistically, the speech tones and the acoustic correlate of the corresponding drum representations have a significant positive relationship. In both spoken and drum communication, vowel and consonant-vowel prosodic units have different statuses. To conclude, Yorùbá drummers communicate via the gángan drum by transposing certain phonemic features of their language to musical forms.